2014
DOI: 10.1016/j.molcel.2014.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis and Regulation of OTULIN-LUBAC Interaction

Abstract: SummaryThe linear ubiquitin (Ub) chain assembly complex (LUBAC) generates Met1-linked “linear” Ub chains that regulate the activation of the nuclear factor κB (NFκB) transcription factor and other processes. We recently discovered OTULIN as a deubiquitinase that specifically cleaves Met1-linked polyUb. Now, we show that OTULIN binds via a conserved PUB-interacting motif (PIM) to the PUB domain of the LUBAC component HOIP. Crystal structures and nuclear magnetic resonance experiments reveal the molecular basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
242
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(257 citation statements)
references
References 37 publications
9
242
1
Order By: Relevance
“…Thereby OTULIN can only cleave peptide bonds present in M1-linked chains (Keusekotten et al, 2013;Rivkin et al, 2013). This M1-linked-chain-specific OTULIN interacts with HOIP, the catalytic core subunit of LUBAC, forming a functional complex that regulates the production of linear chains (Elliott et al, 2014;Schaeffer et al, 2014). Besides OTULIN, USP10 (Niu et al, 2013) and the cylindromatosis tumor suppressor (CYLD) have been shown to counteract LUBAC-mediated linear ubiquitylation.…”
Section: M1 Linkages -Key Regulator In Nf-κb Signalingmentioning
confidence: 99%
“…Thereby OTULIN can only cleave peptide bonds present in M1-linked chains (Keusekotten et al, 2013;Rivkin et al, 2013). This M1-linked-chain-specific OTULIN interacts with HOIP, the catalytic core subunit of LUBAC, forming a functional complex that regulates the production of linear chains (Elliott et al, 2014;Schaeffer et al, 2014). Besides OTULIN, USP10 (Niu et al, 2013) and the cylindromatosis tumor suppressor (CYLD) have been shown to counteract LUBAC-mediated linear ubiquitylation.…”
Section: M1 Linkages -Key Regulator In Nf-κb Signalingmentioning
confidence: 99%
“…Three PUB-domain containing proteins have been described so far in humans and all interact with the p97 C-terminal tail: PNGase (peptide N-glycanase) [85,86], which is involved in the deglycosylation of misfolded glycoproteins [87], the UBX protein UBXD1 [68,85,88], and HOIP (HOIL-1-interacting protein) [89][90][91], the catalytic subunit of the E3 ubiquitin ligase LUBAC, which catalyzes the assembly of linear ubiquitin chains [92]. Molecular insights into the interaction of the PUB domain with p97 were revealed by crystal structures of the PNGase and HOIP PUB domains in complex with peptides comprising the five and four, respectively, C-terminal residues of p97 called PIM (PUB Interacting Motif) [86,91] (Fig.…”
Section: The Pub Domainmentioning
confidence: 99%
“…The PUB-PIM complex is stabilized by a combination of hydrophobic and electrostatic interactions, with a key interaction mediated by insertion of the hydrophobic side chain of Leu804 and the aromatic side chain of Tyr805 of p97 into a hydrophobic pocket of the PUB domain called the U-Y pocket [91]. Interestingly, phosphorylation of the strictly conserved tyrosine residue within the PIM (Tyr805 in p97) completely blocks the interaction of p97 with the PUB domain and with the PUL domain of Ufd3 (see below) [86,90,91,93]. Thus, tyrosine phosphorylation appears to be a conserved mechanism to control protein-protein interactions of the C-terminal tail of p97.…”
Section: The Pub Domainmentioning
confidence: 99%
“…Met1-Ub chains are assembled by the linear ubiquitin chain assembly complex (LU-BAC), composed of HOIP, HOIL-1, and SHARPIN [1]. LUBAC function is regulated by the deubiquitinases (DUBs) OTULIN [2-4] and CYLD [5][6][7], which both associate with the catalytic subunit HOIP [5][6][7][8].Previous studies have revealed that OTULIN exclusively hydrolyzes Met1-Ub, prevents accumulation of Met1-Ub on LUBAC components under basal conditions, and restricts ubiquitination of LUBAC substrates after receptor stimulation [2][3][4]. However, the contribution of OTULIN to regulation of physiological immune responses had not been investigated.…”
mentioning
confidence: 99%
“…Met1-Ub chains are assembled by the linear ubiquitin chain assembly complex (LU-BAC), composed of HOIP, HOIL-1, and SHARPIN [1]. LUBAC function is regulated by the deubiquitinases (DUBs) OTULIN [2-4] and CYLD [5][6][7], which both associate with the catalytic subunit HOIP [5][6][7][8].…”
mentioning
confidence: 99%